Use of Dipstick Test and Sediment Microscopy For Detection of Urinary Tract Infection: Diagnostic Value and Comparison With Urine Culture - Parlaktaş, Bekir Süha; Bulut, Yunus; Özuğurlu, Aziz Fikret (Fırat University, 2003)
Aim: This study aims to test the diagnostic value of reagent-strip and sediment microscopy of urine compared to uroculture and evaluate their use singly or in combination to identify urinary tract infections in suspected cases. Materials and method: 848 patients who admitted to urology department outpatient clinic were included into the study. Urine specimens of all patients were subjected to urine dipstick test, sediment microscopy and culture test. The sensitivity, specificity, and positive (PPV) and negative predictive values (NPV) were determined for each test or combination of tests with respect to urine culture. Performance of urinalysis tests was evaluated by calculation of sensitivity, specificity, PPV and NPV. Statistical analysis was performed by using the chi-square test. Results: Culture was positive in urine specimens of 145 (17.1 %) patients. E.coli (74.5%) was the most frequently isolated microorganism and 8.28 % gram positive cocci, as well. There were statistically significant differences between uroculture and LE, N, sediment microscopy of urine results (p

Amaç: İdrar yolu enfeksiyonu (İYE) tanısı için altın standart olan idrar kültürü yapılamayan durumlarda miyarlı idrar stripleri ile bakılan lökosit esteraz (LE), nitrit redüktaz (N), idrar sediment mikroskopisi kullanımı ve tanısal değerleri tartışmalıdır. Gereç ve yöntem: Bu çalışmada üriner yakınmaları nedeniyle üroloji polikliniğine başvuran 848 hastadan alınan idrar örneklerinin, sediment mikroskopisi, LE ve N tetkikleri sonuçları ile idrar kültürü sonuçlarını karşılaştırdık. İYE için indirekt belirteç olan bu parametrelerin ayrı ayrı ve çeşitli kombinasyonları halinde sensitivite, spesifisite, pozitif prediktif ve negatif prediktif değerleri hesaplandı. Bu değerleri idrar kültürü sonuçları ile karşılaştırıldı. İstatistiksel değerlendirmede ki-kare testi kullanıldı. Bulgular: 145 (%17.1) hastanın idrar örneklerinde bakteri ürediği ve bunların çoğunluğunun (%74.%) E.Coli olduğu tesbit edildi. İdrar kültürü sonuçları ile sediment mikroskopisi, LE, N testleri sonuçları arasında istatistiksel olarak anlamlı fark bulundu (p
İdrar Yolu Enfeksiyonu Tanısında Sediment Mikroskopisi ve İdrar Striplerinin Kullanımı: Tanısal Değerleri ve İdrar Kültürü ile Karşılaştırılması